Catalytic hydrolysis of cellulose to total reducing sugars with superior recyclable magnetic multifunctional MCMB‐based solid acid as a catalyst. Issue 3 (2nd December 2019) - Li, Heng‐Xiang; Shi, Wen‐Jing; Zhang, Xiaohua; Liu, Puxu; Cao, Qing; Jin, Li'e
Abstract: BACKGROUND: Effective cellulose hydrolysis has a huge potential for producing high value‐added biomass‐based platform chemicals, such as glucose, hydroxymethylfurfural, levulinic acid, and total reducing sugars (TRS). Particularly, a magnetic multifunctional solid acid catalyst (Fe3 O4 /Cl–MCMB–SO3 H) was synthesized by loading the active groups on the magnetic mesocarbon microbead (MCMB) derived from the co‐calcination of coal tar pitch and ferroferric oxide, which was applied as a catalyst in the conversion of cellulose into TRS. RESULTS: Given the superior properties of MCMB, a novel magnetic MCMB‐based solid acid with cellulose‐binding domain (–Cl group) and catalytic domain (–SO3 H group) was successfully prepared. Results indicated that this catalyst exhibited superior catalytic activity, recyclability and regenerability, and easy separation from the reactant. The acidic densities of –SO3 H and –Cl in Fe3 O4 /Cl–MCMB–SO3 H reached 1.77 and 1.32 mmol/g, respectively. The 68.6% TRS yield can be obtained from cellulose at 140 °C for 3 h in distilled water by using Fe3 O4 /Cl‐MCMB‐SO3 H as the catalyst. The TRS yield still reached 61.1% after the catalyst was used six times. Importantly, through catalyst regeneration, the –SO3 H density and TRS yield still reached 1.69 mmol/g and 67.3%, indicating that the catalyst exhibited excellent regenerability. CONCLUSION: Such multifunctional magnetic catalyst would be a promising catalyst in the conversion of cellulose into biofuels, which was attributed to the efficient catalytic performance, magnetism, and excellent recyclability and regenerability. © 2019 Society of Chemical Industry